The impact of commercial open source software on proprietary software producers and social welfare - Mingqing Xing (Journal of Industrial Engineering and Management, 2014)
Purpose: A growing number of commercial open source software, based on free open source software, appears in many segments of software market. The purpose of this study is to investigate how commercial open source software affects proprietary software producer’s pricing (market share or profit), consumer surplus and social welfare. Design/methodology: To analyze the impact of commercial open source software on proprietary software producer, this study constructs two vertical-differentiation models: the basic model considers proprietary software only competing with free open source software, and its extended one considers proprietary software competing with both free and commercial open source software. Findings: This study mainly finds that the presence of commercial open source software leads to the software price and profit for proprietary software producer decrease and the consumer surplus and social welfare increase. However, it does not necessarily cause the decline in the market share for proprietary software producer. Originality/value: The main contribution of this study is to examine the effect of commercial open source software on proprietary software producer’s competitive strategy, consumer surplus and social welfare.